Tools for Understanding Nanoscale Lipid Regulation of Ion Channels - Robinson, Carol V.; Rohacs, Tibor; Hansen, Scott B. (Trends in biochemical sciences (Amsterdam. Regular ed.), 2019)
Anionic phospholipids are minor but prominent components of the plasma membrane that are necessary for ion channel function. Their persistence in bulk membranes, in particular phosphatidylinositol 4,5-bisphosphate (PIP2), initially suggested they act as channel cofactors. However, recent technologies have established an emerging system of nanoscale signaling to ion channels based on lipid compartmentalization (clustering), direct lipid binding, and local lipid dynamics that allow cells to harness lipid heterogeneity to gate ion channels. The new tools to study lipid binding are set to transform our view of the membrane and answer important questions surrounding ion channel-delimited processes such as mechanosensation. Mass spectrometry, cryo-EM, and super-resolution microscopy are advanced tools set to evolve the role of phosphatidylinositol 4,5 bisphosphate (PIP2) and other anionic lipids in the regulation of ion channel function.Cells harness lipid heterogeneity to gate a channel.Phosphatidic acid (PA)-regulated channels are an emerging class of lipid-regulated channels.Nanoscale lipid gradients open up the possibility for membrane-resident anionic lipids to centrally coordinate biological processes by locally regulating ion channel function.